2018
DOI: 10.3389/fimmu.2018.01987
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Necrotizing Factor 1 Downregulates CD36 Transcription in Macrophages to Induce Inflammation During Acute Urinary Tract Infections

Abstract: Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) induce cystitis, pyelonephritis, and can cause kidney scarring and failure if inflammation is not under control. The detailed effects of cytotoxic necrotizing factor 1 (CNF1), the key UPEC toxin, on the pathogenicity of UPEC remain unclear. CD36 is an important scavenger receptor, responsible for pathogen and apoptotic cell clearance, and plays an essential role in host immune defense and homeostasis. Regulation of CD36 by bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
(67 reference statements)
1
18
0
1
Order By: Relevance
“…For example, CNF1 promotes bacterial invasion into host cells by activating Rac 37 . Previously, we reported that CNF1 increased prostate cancer cell migration and invasion to promote prostate cancer metastasis through activating Cdc42, 6 and CNF1 reduced macrophage phagocytosis to induce inflammation during acute UTIs partially through Cdc42 38 . Schmidt reported that CNF1 enhanced breast cancer cell invasion through activating RhoC 39 …”
Section: Discussionmentioning
confidence: 97%
“…For example, CNF1 promotes bacterial invasion into host cells by activating Rac 37 . Previously, we reported that CNF1 increased prostate cancer cell migration and invasion to promote prostate cancer metastasis through activating Cdc42, 6 and CNF1 reduced macrophage phagocytosis to induce inflammation during acute UTIs partially through Cdc42 38 . Schmidt reported that CNF1 enhanced breast cancer cell invasion through activating RhoC 39 …”
Section: Discussionmentioning
confidence: 97%
“…In recent years, substantial and growing progress has been made in the field of immunometabolism 33,34 , providing an in-depth understanding of the role of intracellular metabolites (known as immunometabolites) in the complex regulation of immune cells. Macrophages, a main component of innate immunity, play a vital role in host defence and homeostasis 35 . Macrophages are the first line of defence for the immune system and contribute to defence against infection by producing pro-inflammatory factors (such as IL-1β) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The acute pyelonephritis mouse model was established as previously described. 53 The bacteria were cultured overnight in static LB medium at 37 °C. Cultured bacteria were pelleted by centrifugation (5000 × g for 5 min at 4 °C) and resuspended in PBS to obtain a density of 2 × 10 10 CFU/ml.…”
Section: Methodsmentioning
confidence: 99%